Hurricane variation in the eastern North Pacific Ocean in the last 20 years - Mehtab, Muhammad (Prevention and Treatment of Natural Disasters, 2023)
The frequency, severity, and distribution of hurricanes in the Eastern North Pacific Ocean have changed significantly during the last 20 years (2003–2023). This study examines these differences along with trends, environmental factors, and their wider ramifications. The results show that increasing sea surface temperatures and increased ocean heat content contribute to an increase in storm strength, with a greater percentage of significant hurricanes (Category 3 and above). The effects of climate change and natural events like the El Niño-Southern Oscillation (ENSO) are highlighted by changes in storm paths and prolonged seasonal activity. This review highlights the urgent need for coordinated action, combining scientific research, policy interventions, and community resilience strategies to adapt to changing hurricane behavior. Ecosystems like coral reefs and mangroves, which serve as natural storm buffers, are becoming more vulnerable; improvements in forecasting technology and disaster preparedness are essential for reducing these risks in tandem with international efforts to address climate change. The effects on human populations and ecosystems are significant, including increased risks of storm surges, displacement, economic losses, and environmental degradation. The Eastern North Pacific region can more effectively handle the socioeconomic and environmental issues brought on by storms in a warming world by combining these initiatives.